2020
DOI: 10.1177/2055116920907429
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic detection of a feline meningioma using 5-aminolaevulinic acid hydrochloride

Abstract: Case summary The present study describes the case of a feline meningioma that was detected using 5-aminolaevulinic acid hydrochloride (5-ALA)-induced protoporphyrin IX (PpIX) fluorescence at surgery. An extra-axial mass in the temporoparietal region was observed by MRI. Following craniectomy and durotomy, photodynamic detection (PDD) was performed for detection of the tumour. Intratumour PpIX was detected using fluorescence spectrum evaluation and high-performance liquid chromatography. PDD revealed bright flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…2,[9][10][11]18 To avoid these issues, intraoperative magnetic resonance imaging or fluorescenceguided resection have been studied in cat, but involve limitations including the duration of the procedure and possible false-negative staining. 19,20 Additionally, radiotherapy requires numerous anaesthesia events and is not associated with a better prognosis, although it is interesting for tumours in complicated/inoperable locations. 21 To help surgeons visualise the spatial relationship between the lesion and surrounding tissue and hence choose the best surgical route and check the extent of surgical resection, three-dimensional (3D) printing is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[9][10][11]18 To avoid these issues, intraoperative magnetic resonance imaging or fluorescenceguided resection have been studied in cat, but involve limitations including the duration of the procedure and possible false-negative staining. 19,20 Additionally, radiotherapy requires numerous anaesthesia events and is not associated with a better prognosis, although it is interesting for tumours in complicated/inoperable locations. 21 To help surgeons visualise the spatial relationship between the lesion and surrounding tissue and hence choose the best surgical route and check the extent of surgical resection, three-dimensional (3D) printing is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Also, tumour recurrence due to incomplete resection or neoplastic seeding has been suspected in about 20% of cases 2,9–11,18 . To avoid these issues, intraoperative magnetic resonance imaging or fluorescence‐guided resection have been studied in cat, but involve limitations including the duration of the procedure and possible false‐negative staining 19,20 . Additionally, radiotherapy requires numerous anaesthesia events and is not associated with a better prognosis, although it is interesting for tumours in complicated/inoperable locations 21 …”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy is a minimally invasive treatment modality for a variety of malignant diseases and precancerous lesions of skin, breast, esophagus and colon, urinary bladder, head and neck [1][2][3][4][5]. Exogenously administered photosensitizer accumulates in tumors and selectively sensitizes cancer tissue to the laser light.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, we reported the use of 5-ALA-PDD for detecting mammary gland and brain tumours in veterinary medicine. [8][9][10] To the best of our knowledge, however, no study has reported the use of 5-ALA-PDD to detect MM in veterinary medicine. The present study describes the use of 5-ALA-PDD for MM diagnosis in a cat and dog, as well as the effectiveness of intracavitary chemotherapy.…”
mentioning
confidence: 99%
“…Recently, we reported the use of 5‐ALA‐PDD for detecting mammary gland and brain tumours in veterinary medicine 8–10 . To the best of our knowledge, however, no study has reported the use of 5‐ALA‐PDD to detect MM in veterinary medicine.…”
mentioning
confidence: 99%